What Can Queer Theory Do for Intersex? - Morland, Iain (GLQ: A Journal of Lesbian and Gay Studies, 2009)
In this essay I explore how queer theory might account for postsurgical intersex bodies of diminished genital tactility. In other words, I evaluate whether a critique of surgery’s effects is possible from a queer theoretical perspective on the body. I contend that for this purpose queer theory must do more than focus on bodily sensations such as pleasure, shame, and touching. The essay makes four key claims: first, that the desensitized postsurgical body cannot be accounted for by a queer discourse in which sexual pleasure is a form of hedonistic activism; second, that a queer discourse of shame enables a degree of critical engagement with the surgical creation of atypically sensate bodies; third, that pleasure and shame are both queer sensations, and queer theory’s assumption of a sensorial basis to cultural critique, which is exemplified by the queer touch, flounders when confronted with the desensitized intersex body; fourth, that if queer theory is figured as a kind of reaching—but not necessarily touching—then it can be of greater use in accounting for the problematic yet ambivalent effects of intersex surgery.
Keywords: LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; premier cycle; queer; ressource en ligne; thématiques; études culturelles; études littéraires